The Study on Phytochemical and Antimicrobial Activities of Momordica cochinchinensis (Lour.) Spreng. Seeds Extract - Puksee, Parichat; Fakkham, Supalak; Sangvichien, Sanjai; chinakran, Thara; Arnmanee, Peeraya (Princess of Naradhiwas University Journal, 2023)
This research aims to study the phytochemical and antimicrobial activity of Momordica cochinchinensis (Lour.) Spreng. seeds (Gac seed) extracts with hexane and ethanol by testing the activity of inhibiting the microorganisms’ growth with Disc diffusion method. To examine the minimum level of concentration that could inhibit the microorganisms’ growth by using Micro broth dilution method. In addition, to investigate the minimum of concentration that could inhibit the microorganisms’ growth using Spot test method. The results of the study of crude extracts from Gac seeds with ethanol were revealed that there were phytochemical compounds of alkaloids, terpenoids, saponins, and flavonoids but they were not found in crude extracts with hexane and in the study of the inhibitory activity of the microorganisms M. furfur, S. aureus and K. pneumoniae. The determination result of the minimum inhibition concentration of the microorganisms’ growth was revealed that Gac seeds extracts could inhibit M. furfur, S. aureus and K. pneumoniae. Besides, Gac seeds extracts with hexane and ethanol solvents could inhibit and kill M. furfur. The Minimum Inhibitory Concentrations (MIC) value of the microorganisms’ growth was 125 and 15.625 mg/mL, respectively and The Minimum Fungicidal Concentration (MFC) was greater than 125 and 62.5 mg/mL, respectively. In addition, Gac seeds extracts with hexane and ethanol solvents were able to inhibit only S. aureus and K. pneumoniae in which it could promote the utilization of agricultural residues of saccharin and develop a medicinal formulation for the treatment of skin diseases in the future.